Peran Estuaria Sebagai Habitat Penting Bagi Kehidupan Akuatik - zebua, Hertini; Halawa, Eduardus Heronimus (Jurnal Perikanan dan Kelautan, 2025)
Estuaries are transitional ecosystems between freshwater and marine environments, characterized by high productivity and complex biodiversity. This study aims to analyze the physical, chemical, and biological characteristics of estuarine ecosystems and identify the impact of anthropogenic activities on environmental quality and community structure. A descriptive quantitative method was applied through field observations and laboratory analysis across three estuarine zones (upstream, middle, and downstream). The results show environmental gradients, with increasing salinity and nutrient levels from upstream to downstream. Communities of phytoplankton, zooplankton, macrozoobenthos, and fish displayed distribution patterns influenced by local environmental conditions. Decreasing dissolved oxygen and rising nitrate and phosphate concentrations indicate anthropogenic pressures that may degrade ecosystem quality. Therefore, sustainable estuarine management is necessary to maintain ecological balance and ecosystem services.